Development of immunity in natural Plasmodium falciparum malaria: antibodies to the falciparum sporozoite vaccine 1 antigen (R32tet32). - Webster, H K (1987)
Antibodies that reacted with a candidate sporozoite vaccine antigen (R32tet32) were found in 20 of 21 patients treated for acute infection with Plasmodium falciparum and monitored longitudinally over 67 days. R32tet32 contains 32 tandem copies of a tetrapeptide sequence that constitutes the immunodominant epitope of the circumsporozoite surface protein. The magnitude of the antibody response varied considerably among individuals and appeared to be independent of the number of previous clinical infections. Recrudescence of infection or infection with Plasmodium vivax had no demonstrable effect on antibody levels, although reinfection with P. falciparum produced a rapid rise in antibody titer. Antibody levels were observed to decline rapidly after treatment of clinical infection with mefloquine. The apparent antibody half-life was 27 days, which is comparable to the half-life of circulating immunoglobulin G in humans. The data suggest that antisporozoite antibody production ceased on about day 4 after treatment of acute infection. A similar pattern of response was observed for antibodies against the erythrocytic forms of the parasite. The cessation of antibody synthesis was interpreted as being due to immunosuppression induced by the presence of intraerythrocytic parasites and may explain in part why protective immunity is poorly developed in natural malaria infections.